E - Jihan Athaaya; Erlita Ridanasti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The adoption of ShopeePay digital payment technology by Indonesian MSME merchants still faces various barriers despite offering operational convenience. This study aims to analyze factors influencing MSME merchants' intention to use ShopeePay using the Technology Acceptance Model (TAM). Six hypotheses regarding the influence of perceived ease of use, perceived usefulness, perceived cost, perceived trust, word-of-mouth learning, and perceived experience on usage intention were tested through 180 valid questionnaires from MSME merchants across five Indonesian provinces. Data analysis employed Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. Results show that perceived ease of use and perceived experience positively influence usage intention through the mediation of perceived experience. perceived trust and word-of-mouth learning have significant positive effects, while perceived cost significantly influences merchant usage intention. Perceived experience proves to have a positive influence on merchant usage intention. This study contributes to marketing literature on digital service adoption by MSMEs, particularly in the context of digital payments.